Preparing Teacher Coordinators to Conduct Cooperative Work Experience Education. - National Child Labor Committee, New York, NY.; National Child Labor Committee, New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
The National Child Labor Committee (NCLC), having as its goal the improvement and increased utilization of Cooperative Work Experience Education (CWEE), conducted several studies to identify areas in which improvement is desirable and attainable. Based on information collected and knowledge of job demands, nine changes to preparation of teacher/cordinators are recommended. Part I describes a two-year study to determine how to improve and extend the use of cooperative education. Data for the study included: curriculums from 26 schools of education; descriptions of tasks performed by teacher/coordinators and estimates of relative importance of each task; contents of manuals and guides for conduct of cooperative education issued by 11 state departments of education and one Canadian provincial department; and findings and recommendations in studies and articles relative to teacher training. Part II outlines a curriculum that was developed. The curriculum contains a course sequence to prepare teacher/coordinators and an outline for each course. The six courses outlined include Introduction to CWEE, Administration of CWEE, Coordinating and Integrating Cooperative Education Activities, Improving Learning Opportunities at the Workplace, Cooperative Education for Special Student Populations, and Obtaining and Using Labor Market Information in Planning and Conducting Cooperative Education. Each course includes goals, objectives, content, teaching methods, and resources. The third part of this document is a syllabus for the introductory course in CWEE. It serves as an example of how the syllabus should be prepared for each of the courses in teacher/coordinator preparation. Appendixes include a bibliography, questionnaire to schools of education, key elements of CWEE, matrix of the key elements in college curricula, matrix of the importance of the elements, and elements for training teacher/coordinators. (KC)
Availability: National Child Labor Committee, 1501 Broadway, Suite 1111, New York, NY 10036 ($4.00; 10 or more--20 percent discount).
Sponsoring Agency: Mott (C.S.) Foundation, Flint, MI.
Sponsoring Agency: Edna McConnell Clark Foundation, New York, NY.
Sponsoring Agency: Atlantic Richfield Foundation, New York, NY.
Teachers.
Practitioners.
Keywords: College Programs; Cooperative Education; Course Content; Course Organization; Educational Needs; Experiential Learning; Field Experience Programs; High Schools; Higher Education; Job Training; Preservice Teacher Education; Program Improvement; School Business Relationship; Teacher Role; Work Experience Programs; Guides, Non-Classroom.